Domestic Violence in Bulgaria - Statistics and Facts. Legislation and Protection - Makeva, Blagorodna (Law Journal of New Bulgarian University, 2024)
The article includes an analysis and assessment of the legal framework, as well as an overview of the amendments and supplements in the Protection from Domestic Violence Act, legislative gaps and weaknesses and the need for amendments, policies and service provision, and good normative and organizational practices. The analysis and recommendations have been developed after an in-depth analysis of the situation in the Republic of Bulgaria and contain statistical data related to the phenomenon of domestic violence. The analysis is based on data which include the number of calls to the single European number 112, the protection orders received for control in the regional police stations and the pre-trial proceedings initiated for crimes committed in the conditions of domestic violence.